2010
DOI: 10.1074/jbc.m110.128645
|View full text |Cite
|
Sign up to set email alerts
|

Type I Transglutaminase Accumulation in the Endoplasmic Reticulum May Be an Underlying Cause of Autosomal Recessive Congenital Ichthyosis

Abstract: Type I transglutaminase (TG1) is an enzyme that is responsible for assembly of the keratinocyte cornified envelope. Although TG1 mutation is an underlying cause of autosomal recessive congenital ichthyosis, a debilitating skin disease, the pathogenic mechanism is not completely understood. In the present study we show that TG1 is an endoplasmic reticulum (ER) membrane-associated protein that is trafficked through the ER for ultimate delivery to the plasma membrane. Mutation severely attenuates this processing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 87 publications
1
4
0
Order By: Relevance
“…In order to confirm that collagen accumulation was a result of defective intracellular transport, 10 mM brefeldin A (BFA), an ER-Golgi transport inhibitor, was added to the culture media, and total cellular lysates were obtained 23 hr after treatment. 18 Addition of BFA caused the accumulation of intracellular type I collagen, similar to what was observed with ARCN1 KD (Figure 4B). Interestingly, BFA treatment reduced the amount of ARCN1 in the cells (Figure 4B).…”
supporting
confidence: 79%
“…In order to confirm that collagen accumulation was a result of defective intracellular transport, 10 mM brefeldin A (BFA), an ER-Golgi transport inhibitor, was added to the culture media, and total cellular lysates were obtained 23 hr after treatment. 18 Addition of BFA caused the accumulation of intracellular type I collagen, similar to what was observed with ARCN1 KD (Figure 4B). Interestingly, BFA treatment reduced the amount of ARCN1 in the cells (Figure 4B).…”
supporting
confidence: 79%
“…Transglutaminase 1 ( TGM1 ) is a key enzyme in keratinocyte differentiation (Elias et al., ; Russell et al., ; Thacher & Rice, ) and was downregulated in AR‐exposed bobcats. Mutations in this gene result in deficient epidermal cornification (Herman et al., ) and inhibited skin cell maturation (Jiang et al., ). Second, stratifin ( SNF ) is also downregulated in AR‐positive bobcats.…”
Section: Discussionmentioning
confidence: 99%
“…28 The p.Arg307Gly mutation was also found in our SICI patient in the heterozygous state and in another SICI patient in the homozygous state described by Hackett et al 15 This mutation, therefore, is common to 3 phenotypes. In keratinocyte cell cultures, Jiang et al 29 have recently shown that the TGM1 protein is associated with the endoplasmic reticulum and ultimately delivered to the plasma membrane; the p.Cys377Ala mutation led to the accumulation of the TGM1 protein in the endoplasmic reticulum and the absence of normal trafficking and delivery to the plasma membrane.…”
Section: Commentmentioning
confidence: 99%